Pengurangan Dosis Pupuk pada Produksi Sawi Hijau Organik dengan Pergiliran Tanaman Jagung dan Kedelai - Kurniawati, Ari; Melati, Maya; Aziz, Sandra Arifin; Purwono, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The application of organic fertilizer and crop rotation are combination of cultivation system integrally to preserve land fertility. This study aimed to determine the effect of crop residues produced in the first season to reduce organic fertilizer rate for mustard greens cultivation in the second season. The experiment was conducted at IPB organic farm, Cikarawang, Darmaga in April until June 2015. The first season was the first experiment conducted separately for soybean and corn to study different manure types for both crops which the rate of each manure was 20 ton ha-1 for soybean and 25 ton ha-1 for corn. Soybean and corn residues were used in the following season on mustard green cultivation. The experimental design was split plot design with crop residues as main plot, and combination of manure types (chicken, cow, goat) and rates (0, 10 ton ha-1) as sub plot. Data were analyzed using variance. Means were statistically compared with Tukey test at α < 0.05 level. The results showed that the soybean and corn residues can be used as nutrient sources for mustard greens cultivation. The application of manure was not necessary for mustard greens cultivation if soybean or corn residues were added in the second season and there was residues from manure in the first season.Keywords: chicken manure, cow manure, crop residue, goat manure